Evaluasi Keragaan Kelompok Binaan Di Daerah Penyangga Bagian Selatan Taman Nasional Bunaken - Meylan Karundeng; Hengki D. Walangitan; Johny S. Tasirin (Sam Ratulangi University, 2022)
This study aims to describe as well to evaluate the performance of the fostered groups in the southern buffer zone of the Bunaken National Park. This research was conducted from April to June 2022. The research method used is semi-quantitative analysis where data collection is carried out using a questionnaire to see the indicators of Institutional Management, Estate Management and Business Management of each target group based on the Regulation of the Minister of Environment and Forestry PP.89/MENLHK/SETJEN/KUM.1/8/2018 concerning Forest Farmer Groups. The selection of respondents was done intentionally, who are the administrators and members of the Bunaken National Park Center assisted groups, namely: Cahaya Trans, Singkanaung, Mutirara Kreatif, Minaesa Sylva Jaya and Cahaya Tatapaan. The results of the interview will be verified with physical evidence in the form of Minutes, Decision Letters, Attendance and so on. The results showed that the dynamics of the different assisted groups fluctuated so that they needed social engineering to improve their performance, while for the performance assessment the Minaesa Sylva Jaya group with a score of 10.53 or the Less category, while for the three groups it was in the Enough category; Mutiara Kreatif (54.39), Cahaya Trans (47.37), and Singkanaung (33.33) while Cahaya Tatapaan with a score of 65.79 or included in the Good category. prevent a vacuum and maintain the continuity of the community empowerment program in the southern buffer area of Bunaken National Park.